The making of the Pentecostal melodrama religion, media and gender in Kinshasa - Pype, Katrien (New York : Berghahn Books, 2012)
How religion, gender, and urban sociality are expressed in and mediated via television drama in Kinshasa is the focus of this ethnographic study. Influenced by Nigerian films and intimately related to the emergence of a charismatic Christian scene, these teleserials integrate melodrama, conversion narratives, Christian songs, sermons, testimonies, and deliverance rituals to produce commentaries on what it means to be an inhabitant of Kinshasa.
Illustrations; Acknowledgments; On Language; Chapter 1 -- The First Episode; Chapter 2 -- Cursing the City: The Ethnographic Field and the Pentecostal Imagination; Chapter 3 -- New Fathers and New Names: Social Dynamics in an Evangelizing Acting Group; Chapter 4 -- Variations on Divine Afflatus: Artistic Inspiration, Special Effects, and Sermons; Chapter 5 -- Mimesis in Motion: Embodied Experiences of Performers and Spectators; Chapter 6 -- The Right Road: Moral Movements, Confessions, and the Christian Subject
Description based on print version record.
Keywords: Motion pictures in ethnology -- Congo (Democratic Republic) -- Kinshasa; Video recording in ethnology -- Congo (Democratic Republic) -- Kinshasa; Anthropology of religion -- Congo (Democratic Republic) -- Kinshasa; Pentecostal churches -- Congo (Democratic Republic) -- Kinshasa; Television in religion -- Congo (Democratic Republic) -- Kinshasa; Kinshasa (Congo) -- Religious life and customs; Kinshasa (Congo) -- Social condtions; Kinshasa (Congo) -- Politics and government; PERFORMING ARTS / Television / Reference; Electronic books